2017
DOI: 10.1186/s13071-017-2227-0
|View full text |Cite
|
Sign up to set email alerts
|

Developing a mathematical model for the evaluation of the potential impact of a partially efficacious vaccine on the transmission dynamics of Schistosoma mansoni in human communities

Abstract: BackgroundThere is currently no vaccine available to protect humans against infection with the schistosome digenean parasites, although candidate formulations for Schistosoma mansoni are under trial in animal models, including rodents and primates. Current strategies for the control of infection are based on mass drug administration (MDA) targeted at school-aged children of age 5 to 14 years. This approach is unlikely to eliminate exposure to infection except in settings with very low levels of transmission.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…The macroparasite transmission dynamics model for the transmission of the parasite to measure outcomes in human populations has predicted that an Sm-p80-based vaccine has the potential to contribute greatly to reducing the burden of schistosomiasis and parasite transmission in endemic regions. 10 Immunolocalization analyses of confocal images demonstrated that Sm-p80 protein is distributed in and on the surface epithelial syncytium of adult worms, with a 2.5-fold increased intensity (P < 0.001) in Sm-p80-specific fluorescence in female worms compared with male counterparts. Given that Sm-p80 is the vaccine antigen, we postu-late that the upregulation and increased accessibility of Sm-p80 renders female worms more susceptible than male worms to immune-mediated killing.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The macroparasite transmission dynamics model for the transmission of the parasite to measure outcomes in human populations has predicted that an Sm-p80-based vaccine has the potential to contribute greatly to reducing the burden of schistosomiasis and parasite transmission in endemic regions. 10 Immunolocalization analyses of confocal images demonstrated that Sm-p80 protein is distributed in and on the surface epithelial syncytium of adult worms, with a 2.5-fold increased intensity (P < 0.001) in Sm-p80-specific fluorescence in female worms compared with male counterparts. Given that Sm-p80 is the vaccine antigen, we postu-late that the upregulation and increased accessibility of Sm-p80 renders female worms more susceptible than male worms to immune-mediated killing.…”
Section: Discussionmentioning
confidence: 94%
“…Using these data and incorporating inhibitory effects on parasite mortality, fecundity, and infection transmission, mathematical modeling was used to predict the overall potential efficacy of our vaccine on disease transmission dynamics. The macroparasite transmission dynamics model for the transmission of the parasite to measure outcomes in human populations has predicted that an Sm‐p80‐based vaccine has the potential to contribute greatly to reducing the burden of schistosomiasis and parasite transmission in endemic regions …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since their inception, substantial improvements in computational power have allowed the use of individual-based models to efficiently sample their resulting distributions over time and overcome the inherent noise in the dynamics. An alternative approach using deterministic compartment-based models, has been used to investigate the effects of vaccination, but this approach allows for less scope for including biological complexity [22, 23]. The transmission cycle, which is related to previously published models [11, 21, 24], is as follows:

Mature adult schistosomes reproduce within human hosts monogamously.

…”
Section: Methodsmentioning
confidence: 99%
“…of human hosts in population, N 1000Baseline prevalence in SACHigh-transmission setting, 65%; Moderate-transmission setting, 45% (Obtained by scaling the contact rate between human hosts and the reservoir)Age-dependent contact with reservoirAges 0–4: 0.032; 5–9: 0.162; 10–14: 1.0; 15+: 0.05[43]Shape parameter α of Gamma distributed risk factor0.24[43]Kato–Katz test aggregation parameter, k 0.87[44, 45]Exponential fecundity decay, z 0.0007/worm[23, 46]Maximum fecundity, λ0.14 egg counts/female worm[45, 47]Average worm life-span5.7 years[48]Human demographyBased on Kenya’s demographic profile[49] …”
Section: Methodsmentioning
confidence: 99%